RELATIONSHIP BETWEEN ACCOMPLISHMENT AND MORPHOLOGICAL CHARACTERISTICS OF STUDENTS IN TEACHING PHYSICAL EDUCATION - Dragan Martinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
This research has measured the relationship and correlation between two categories. This relationship is shown by correlation coefficient (r) on a 1.00 to - 1.00 scale. The 0 correlation coefficient points to no relation between categories. The higher the correlation coefficient, the greater the relation (correlation). The sample of students researched was 1002